Synthesis of Fe(II)/Co(II)-Fused Triphenyl Porphyrin Dimer as Candidate for Oxygen Reduction Reaction Catalyst - Atmanto Heru Wibowo; Anggit Pradifta; Abu Masykur; Ken-ichi Yamashita; Yosuke Tani; Ari Yustisia Akbar; Takuji Ogawa (Indonesian Journal of Chemistry, 2021)
This paper reports the synthesis of Fe(II)/Co(II) fused triphenyl porphyrin dimers as candidate of hybrid organic metal electrocatalyst. The synthesis was conducted in five-step reactions using the starting materials pyrrole and benzaldehyde. The fuse oxidative reaction was done via free-base form of triphenyl porphyrin to omit metal insertions/removals of intermediate products. This strategy is very beneficial for the synthesis of metal fused triphenyl porphyrin that needs less reactions where phenyliodine(III) bis(trifluoroacetate) (PIFA) was successfully deployed in the oxidative reaction of two free-base triphenyl porphyrins. Here, the comparisons of NMR spectra were presented to see the changes of the starting material to the product. Initial electrochemical tests showed that reduction current of planar structure of Fe/Co fused triphenyl porphyrin dimer was on the potential range at -1.10 V to 0.45 V vs Au. Fe-fused triphenyl porphyrin dimer with 7.58 × 10–4 A (-1.05 V) showed slightly better performance than Co-fused triphenyl porphyrin dimer with 5.67 × 10–4 A (-0.97 V).